Tinjauan Sosio-Legal terhadap Pembatalan Hibah Orang Tua kepada Anak dalam Perspektif Hukum Islam di Indonesia - Nabila Raihana; Clara Oktaviana; Herfita Ayu Nayla; Kurniawati Dwi Desriana; Sulistiowati Sulistiowati; Dyah Hayu Woro Indrasti; Najwa Aulia Widyaningrum; Ersy Aulia Anggraeni (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Hibah is a form of voluntary gift given by a person to another while the giver is still alive. In practice, hibah often leads to legal issues, especially when a revocation occurs, which frequently results in disputes between the donor and the recipient. This study employs a normative approach using qualitative methods to examine the causes and legal implications of hibah revocation, as well as the requirements that must be fulfilled for the revocation to be legally valid under Islamic law. The findings indicate that revocation is permissible under certain conditions, such as when the hibah contradicts its intended purpose, exceeds one-third of the donor’s assets, or the recipient commits a breach of agreement. In Islamic law, there are differing opinions among schools of thought regarding the permissibility of revoking hibah given to one’s child. However, according to the Compilation of Islamic Law (KHI), parents have the right to revoke a hibah at any time. The legal consequences of revoking a hibah include the loss of ownership rights over the gifted property, potential family conflicts, and prolonged litigation processes. Therefore, a comprehensive understanding of the legal terms and conditions of hibah is essential to avoid future disputes.